CD24 recruits tumor-associated neutrophils to promote the progression of hepatocellular carcinoma - Jun Wang; Jing Xiong; Yu Cheng; Yuan Wu; Shu Jiang; Huimin Zhang; Xiang Xiao; Hanning Li; Yimeng Liu; Jiapeng Li; Jincheng Wang; Zetao Song; et al. (Journal for ImmunoTherapy of Cancer)
Background The immunosuppressive tumor microenvironment is a significant challenge in the treatment of hepatocellular carcinoma (HCC), necessitating the urgent development of strategies to mitigate its effects.Methods The application of bioinformatics methods to predict the expression level of CD24 in HCC and its relationship with the occurrence and development of HCC. Gene-engineered mice and flow cytometry were used to study the immune cell populations regulated by CD24. Cell metabolism analysis, western blotting, and lactate content measurement were employed to assess the impact of CD24 on lactate secretion by HCC cells. Additionally, cell counting kit 8 and colony formation assays were conducted to evaluate the effect of CD24 on the sensitivity of HCC cells to sorafenib. The integration of RNA sequencing, flow cytometry, cell chemotaxis experiments, and ELISA established a robust framework for understanding CD24-mediated neutrophils immune infiltration.Results In this study, we found that CD24 can recruit neutrophils to infiltrate HCC tissues to form tumor-associated neutrophils (TANs) and polarize TANs to a protumor phenotype by promoting lactate secretion by HCC cells, thus promoting the progression of HCC. In addition, targeting CD24 can enhance the sensitivity of HCC cells to sorafenib by reducing the accumulation of TANs.Conclusions Our results reveal the molecular mechanism by which CD24 promotes HCC progression through recruitment of neutrophils infiltrates, raising new insights into the role of targeting CD24 in driving HCC immunotherapy.